Hybrid Sling for the Treatment of Concomitant Female Urethral Complex Diverticula and Stress Urinary Incontinence - Ito WE; Pastre Marcon PR; Tannouri Garbin AF; Freitas Rodrigues MA; Maia de Almeida SH (Research and Reports in Urology, 2020)
William Eduardo Ito, Paulo Ricardo Pastre Marcon, André Fernando Tannouri Garbin, Marco Aurélio Freitas Rodrigues, Sílvio Henrique Maia de Almeida Surgery Department, Urology Discipline, Universidade Estadual de Londrina, Londrina, PR, BrazilCorrespondence: Sílvio Henrique Maia de Almeida Tel/ Fax +55-43-33771800Email salmeida@sercomtel.com.brAbstract: This study aims to present an alternative technique with the use of a transobturator hybrid sling (autologous fascia lata with a synthetic sling) in two patients with complex urethral diverticulum (CUD), urinary stress incontinence (SUI) and a large incisional infraumbilical hernia. Staged procedures could be performed, but considering the risk of persistence or worsening SUI, and no standard management strategy of SUI associated with CUD; simultaneous treatment was proposed. It is preferable to use autologous materials in such cases. However, the presence of incisional hernia protruded with its content covering the suprapubic area prohibits the retropubic sling technique due to visceral lesion risk. The diverticulum and SUI were repairs in the same surgery using a hybrid transobturator. The technique used for obtaining the fascia lata followed the literature, and a 6 cm segment was acquired. The patients were re-prepared in a lithotomy fashion, and diverticulectomy was performed. The segment of fascia lata was fixed to the mesh and sling was manipulated so that its middle part (fascia) rested directly below the urethra. After 6 months post-operatively, patients referred significant improvement in urinary symptoms. Patients have not had any storage symptoms, International Consultation on Incontinence Questionnaire – Short Form = zero, no SUI, and have not had any mesh-related complications. In conclusion, the present study evaluated a new technique for the treatment of CUD with SUI in a particular clinical scenario. Other studies with extended follow-up periods and larger sample sizes should be performed in this subset of patients.Keywords: urethra, diverticulum, stress urinary incontinence, sling, diverticulectomy, fascia lata